Atividade antinociceptiva, orofacial e anti-inflamatória do óleo essencial de Stachys Lavandulifolia Vahl. (Laminaceae) e de (-)-a-Bisabolol, seu componente majoritário, em roedores - Amarante, Rosana Silva (2017)
Stachys lavandulifolia Vahl (Lamiaceae) is a medicinal plant widely used in Turkey and in Iranian folk medicine because of its analgesic and anti-inflammatory properties. The objective of this study was to evaluate the antinociceptive and anti-inflammatory effects of the essential oil of S. lavandulifolia (EOSl) and (-)-a-bisabolol (BIS), its main compound, in mice. Chromatographic analysis of EOSl showed the presence of (-)-a-bisabolol (56.4%), bicyclogermacrene (5.3%), d-cadinene (4.2%) and spatulenol (2.9%) as main compounds. Male Swiss mice were pretreated with EOSl (25 or 50 mg/kg, po), BIS (25 or 50 mg/kg, po), morphine (3 mg/kg, ip) or vehicle (saline solution 0.9% with two drops of tween 80). Formalin (20 µl, 2%), capsaicin (20 µl, 2.5 µg) or glutamate (20 µl, 25 µm) were injected into the right upper lip of the mice. The anti-inflammatory profile of EOSl or BIS (50mg/kg) was evaluated by the carrageenan-induced inflammatory response (2% in 0.2mL) (pleurisy model) (CEPA/UFS # 72/2015). Data were expressed as mean ± S.E.M. and the difference between groups was analyzed by ANOVA (one-way) with Tukey post-test (p<0.05 was considered significant). Treatment with EOS1 and BIS showed significant inhibitory effects (p<0.05 or p<0.01 or p<0.001) in different orofacial nociception tests, but BIS was effective, significantly reducing nociceptive behavior in all the tests including both phases of the formalin test. The analgesic effect is not related to any anomaly, since the mice treated with EOSl or BIS did not present change in performance in the grip strength. In addition, EOS1 and BIS presented a significant anti-inflammatory effect (p<0.001) in the pleurisy model, which seems to be related to a significant (p <0.05) reduction of the pro-inflammatory cytokine TNF-a in BIS treatment, and IL-1ß (p<0.01) on treatment with EOS1. Our results corroborate the use of S. lavandulifolia in traditional medicine as an analgesic, especially in orofacial pain, and anti-inflammatory, which seems to be related to (-)-a-bisabolol, the main compound of EOS1.